Litterature et voyage: la fascination de L'autre - Martins, Otília Pires (2011)
The allurement of travelling is timeless and is characterized by an unquenchable thirst for diversity and an attraction for all that the Other represents. From classical antiquity to our present day world, literature has thrived on this restlessness for roaming from place to place. In the end, travel literature has created and transmitted an image of the Other which is different from Him/Herself yet imbued with fascination and exoticism.